THE ROLE OF THE CLINICAL AND MOLECULAR ASSAYS IN PROSTATE CANCER DETECTION - Mansouri, Fatemeh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
To assess the correlation between the clinical and molecular assays in identify early and robust prostate cancer detection. Early detection, management of cancer and decision about the disease are important for beneficial treatment of prostate cancer. We used a computerized search of the Medline/ PubMed databases with the key words prostate cancer, biomarker, and early detection. Clinical management of cancer is facilitated by a conventional test such as prostate-specific antigen and digital rectal exam for application in clinical practice. Although these tests have significantly reduced the mortality with prostate cancer, but have some drawbacks and false positive rate. Fortunately, there are strong correlations between the clinical and molecular assays in identifying early and robust cancer detection, because molecular assays are less invasive and reliable. The use of genetic markers has the potential to providing useful prognostic or predictive information into clinically useful diagnostic tests to improve clinical decision-making and enhance therapeutic success. Different clinical and molecular assays are for detecting prostate cancer and use the biomarkers as potential tumor markers could be a useful predictor in the screening and monitoring to avoid over treatment prostate cancer.